MEDIATION SATISFACTION OF DIRECT CASH ASSISTANCE RECIPIENTS ON THE INFLUENCE OF PERSONAL, SOCIAL AND APPARATUS PERFORMANCE FACTORS ON THE SUCCESS OF THE MSME-BASED ECONOMY - Ghozali; Mega D. Novita; Setyaasih (GREENOMIKA, 2022)
The purpose of this study was to examine the influence of personal factors, social factors, the performance of village officials on the success of the MSME-based economy, either directly or indirectly mediated by the satisfaction of BLT recipients. This study followed an exploratory, descriptive and explanatory research design. The object of this research is Mojokerto Regency, Sooko District, Kedungmaling Village. Primary data was collected through the distribution of questionnaires. The population of all communities receiving the Village Fund Direct Cash Assistance (BLT-DD) in 2021 is 72 people. Sampling using saturated sampling. The results of the study: 1) Personal factors have a positive and significant effect on the satisfaction of BLT recipients. 2) Social factors have a positive and significant impact on the satisfaction of BLT recipients. 3) The performance of the village apparatus does not affect the satisfaction of BLT recipients. 4) Personal factors have a positive and significant impact on the success of the MSME-based economy. 5) Social factors have a positive and significant impact on the success of the MSME-based economy. 6) The performance of the village apparatus has no effect on the success of the MSME-based economy. 7) The satisfaction of BLT recipients has no effect on the success of the MSME-based economy. 8) Personal factors have an indirect effect on the success of the MSME-based economy mediated by the satisfaction of BLT recipients. 9) Social factors have an indirect effect on the success of the MSME-based economy mediated by the satisfaction of BLT recipients. 10) The performance of the village apparatus has an indirect effect on the success of the MSME-based economy mediated by the satisfaction of BLT recipients.